Java : a beginner's guide - Schildt, Herbert; Coward, Danny (New York : McGraw Hill, 2024)
Thoroughly updated for Java Platform Standard Edition 21, this practical resource uses a proven, step-by-step approach to teach the fundamentals of Java. You will discover how to get started programming in Java from the very first chapter. Written by Java guru Herbert Schildt and updated by Dr. Danny Coward, the book starts with the basics, such as how to create, compile, and run a Java program. From there, you will learn essential Java keywords, syntax, and commands. Java: A Beginner's Guide, Tenth Edition covers the basics and touches on advanced features, including multithreaded programming, generics, Lambda expressions, and Swing. Enumeration, modules, and interface methods are also clearly explained. This proven guide delivers the appropriate mix of theory and practical coding necessary to get readers up and running developing their own Java applications from the ground up or customize existing code.
"Create, compile, and run Java programs today"--Cover.
"Updated and expanded"--Cover.
Includes bibliographical references and index.
Karim International
Keywords: Java (Computer program language).; Computer science